Peran Podcast dalam Meningkatkan Aksesibilitas Informasi Keagamaan di Kalangan Gen Z - Siti Sofiah Rahmawati; Muhammad Miftahur Rahmat Isnaini; Canra Krisna Jaya (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to explore the role of podcasts in increasing the accessibility of religious information among Generation Z (Gen Z) in Indonesia. Gen Z, who were born in the digital era, have unique characteristics as "digital natives" who rely heavily on technology and interactive media to obtain information. With the increasing popularity of podcasts as a flexible and interesting media format, this research uses a qualitative descriptive approach through literature studies and interviews. The research results show that podcasts not only facilitate the accessibility of religious information but also offer a new way of conveying da'wah messages that are relevant and attractive to the younger generation. Podcasts allow listeners to learn about Islamic values ​​in-depth, anytime and anywhere, without time and place restrictions. This study also found that despite challenges such as content quality and the risk of spreading misinformation, the potential of podcasts as a da'wah tool is enormous. This research concludes that the use of podcasts in da'wah can contribute to empowering individuals and communities, as well as creating a more inclusive space for dialogue among the younger generation. The implications of these findings indicate the need for an effective strategy in developing podcast content to ensure that the information conveyed is accurate and useful for the audience.